Pemanfaatan Instagram dalam Pemasaran dan Pelayanan Pelanggan UMKM Pangkas Rambut di Kota Depok - Nadya Nasywa Hanifah; Siti Mutiara Husna; Nur Fujianti; Afifah Latifah Turahma; Nuralisa Nuralisa; Putri Amelia; Suci Ayu Sudari; Dwi Rachmawati; Alfi Maghfuriyah; Noviyanti Noviyanti (Indo Publishing, 2026)
Hair-cutting service MSMEs are one of the businesses growing rapidly in urban areas, yet most micro-scale business owners have not optimally utilised social media as a means of marketing and customer service. This condition results in low business visibility, a limited market reach, and a less optimal effort to build brand image amid increasingly tight competition. This community service activity aims to improve the competitiveness of hair-cutting service MSMEs through a seminar and Instagram social media management training for 15 hair-cutting MSMEs in Depok City. The method used was a seminar session held on Saturday, 18 July 2026, followed by direct one-on-one training and mentoring conducted offline at Jakarta Global University (JGU), covering the creation and optimisation of Instagram Business accounts, training in photo and video content creation using the CapCut application, and strengthening digital customer service through Direct Message and WhatsApp Business. The results showed an increase in partners' understanding and skills in managing their business Instagram accounts, the availability of ready-to-upload promotional content, and improved readiness among partners to respond to customer interactions digitally. Through this activity, hair-cutting MSMEs are expected to gain an initial foundation for independently strengthening their business branding and becoming better prepared to compete in the digital era.